SOME DISPUTES IN THE PRACTICE OF OBSTETRICS - Távara, Luis (2015)
All that exercise science and art of Obstetrics know that pregnancy and childbirth are not a disease. On the contrary are physiological facts presented during the reproductive life of women and as such should go through the most natural circumstances.